(untitled) (IJM: Journal of Multidisiplinary, 2025)
Hernia Nucleus Pulposus (HNP) is a degenerative condition that commonly occurs in the elderly due to the aging process and decreased elasticity of the intervertebral discs. This case study aims to evaluate the impact of McKenzie Exercise as an intervention for mobility disorders in elderly individuals with HNP. The implementation includes education on McKenzie Exercise application, demonstration, and McKenzie Exercise training designed to reduce lower back pain, improve spinal flexibility, and enhance posture. The results indicate that the client's pain complaints have decreased, the client is able to maintain a sitting position, and can walk to the toilet with assistive devices. This indicates that the implementation of McKenzie Exercise has a positive impact on reducing pain levels and improving functional ability in elderly individuals with Hernia Nucleus Pulposus (HNP). The exercise has been proven effective in alleviating discomfort and assisting elderly patients in regaining mobility. It is hoped that this intervention can continue to be practiced independently by family members, supporting better long-term care. With family support in the application of these exercises, the quality of life for elderly individuals with Hernia Nucleus Pulposus is expected to improve, allowing them to live more independently and comfortably in their daily lives.